Maternal and Fetal Outcome between Dated and Post-dated Pregnancy: A Comparative Study Conducted in a Tertiary Care Hospital (Journal of Shaheed Suhrawardy Medical College, 2023)
This prospective observational comparative study was conducted in department of Obstetrics and Gynaecology (OBGyn) of Shaheed Suhrawardy Medical College Hospital (ShSMCH), Dhaka. It was carried out from April 2019 to September 2019. The objectives was to compare the feto-maternal outcome of postdated pregnancy (40+1- 41+6 weeks) with pregnancy at term(37-40 weeks). Pregnant women admitted in ShSMCH with or without labour pain were considered as study population. Following ethical clearance from the local ethical committee and written informed consent, 59 cases of post-dated pregnancy (case) and 59 cases of term pregnancy (control) were included inthis study. Cases and control were selected by random sampling method according to inclusion and exclusion criteria. Inclusion criteria were: 1) Patients who have excellent EDD(dated by early ultrasonogram) , 2) Patients having regular menstrual cycle prior to present pregnancy and can remember exact LMP, 3) Postdated pregnancy as case and pregnancy at term as control. Exclusion criteria were: 1) Patients with eclampsia, systemic hypertension, heart disease, diabetes mellitus and renal disease, 2) Patients with multiple gestation and any congenital anomaly, 3) Pregnancy occurred during lactational amenorrhoea, 4) Pregnancy with veneral disease, 5) pregnancy with blood group incompatibility. Data were collected with a pre-designed structured questionnaire. A full assessment were done by history[age, occupation, menstrual and obstetric history, medical, surgical and family history, antenatal care(ANC)], physical examination (general, abdominal and vaginal) and ultrasonogram (USG) to assess gestational age and liquor volume. After proper counselling, induction of labour given to patients without labour pain and fetal distress. Mode of delivery, post-delivery maternal and fetal outcome and complication were recorded.This study showed that maximum number of patients in term pregnancy (control) belonged to age group (21-30 years) [control 71.2%, case 62.7%] and in post-dated pregnancy (case) belonged to >30 years [control 15.5%, case 23.7%]. In both groups, maximum number of women were housewives, control 48(81.4%), case 46(78%) and service-holder 11(18.6%) in control, 13 (22%) in case. In control group 36 (61%) were primi-gravida and 23 (39%) were multi-gravida. In case group 29(49.2%) were primi-gravida, 30(50.8%) multi-gravida. Family history of post-dated pregnancy were present in 14(23.7%) of control group and 13(22%) of case group. Most of the women of both control (93.2%) and case (89.8%) received regular ANC. Large fetus were seen in 6(10.2%) of control and 9(15.3%) of case group. Vertex was common presenting feature in both control (94.9%) and case (88.1%). Liquor volume was adequate in maximum number of women of both control (69.5%) and case (62.7%) group. Uterine irritability was present in 16(27.1%) of control and 17 (28.8%) of case group. Associated complication, such as CPD and elderly primi were present in 10 (16.9%) of control and 9 (15.3%) of case group. Induction of labour was required in 33(55.9%)of control and 41 (69.5%) of case group. Normal vaginal delivery was achieved in 41 (69.5%) of control and in 33 (55.9%) of case group women. LSCS required in 18 (30.5%) of control and 25 (42.4%) of case group women. Cause of LSCS is fetal distressin (54.5%) of control and (42.4%) of case group. Post-operative complication were more in case (16.9%), versus (3.4%) in control. Fetal complication were more in case group (22%), versus control (6.8%) regarding birth asphyxia, RDS, neonatal jaundice, neonatal septicemia, meconium aspiration syndrome, macrosomia and neonatal death. So this study showed that maternal and fetal perinatal morbidiy were quite high in post-dated pregnancy. There is scope for further improvement of clinical care practices of post-dated pregnant womenwith acceptable maternal and fetal outcome.J Shaheed Suhrawardy Med Coll 2021; 13(2): 130-136